Causes of stress toward human resource employees: a case study in Menara TM Berhad / Norfatihah Mat Nawi - Mat Nawi, Norfatihah (Faculty of Business and Management, 2008)
The research is study about the causes of stress toward Human Resource employees at Level 10 in Menara Telekom Malaysia, Pantai Bharu. The scope will be focus on the role conflict and role ambiguity, work overload and work under load, feeling inadequacy and changes against work environment, technology, working life and job title. Stress denotes the cause of disruption, the disruption itself and the consequences of that disruption. It is defined as any adjustive demand tone’s physiological and psychological reaction to a challenge imposed on him or her, which requires coping behaviors. From the theoretical framework, the causes of stress is dependent variable that the variable of primary interest to the researcher while the variance in dependent variable can be explained by four independent variables which are role conflict and ambiguity, work overload and work under load, feeling of inadequacy and changes. Role conflict occurs when conflicting roles are required to be carried out by an individual member within an organization. Faced with mutually exclusive expectations, the member experiences role conflict and cannot make a proper judgment about which one to satisfy. Work overload and work under load is employees are need to work overtime for make sure the organization can achieve their target demand with time given and there will never be enough time to do everything that needs to be done. Feeling of inadequacy is instability emotion from individual himself or herself and last but not least is changes either from work environment, working life, technology and job title.